Bibliographic Coupling Indicators for the evaluation of theoretical-methodological proximity in academic genealogy networks a study applied to the PQ fellowship researchers descending from Aldo Barreto - Castanha, Rafael Gutierres [UNESP]; Cabrini Grácio, Maria Cláudia [UNESP] (Universidade Estadual de Campinas, 2020)
This study analyzes the contribution of the Bibliographic Coupling Method to evaluate the transmission strength of the theoretical-methodological current of a researcher among his academic descendants. The universe of analysis was the set of PQ fellowship doctors supervised by Aldo Barreto, Senior PQ researcher in the area of Information Science. The methodological procedure retrieved the set of articles published by Aldo Barreto and his PQ scholarship descendants. Next, we identified the authors cited in this research corpus and calculated the normalized rates of Author Bibliographic Coupling between Aldo Barreto and the analyzed descendant researchers. The strongest theoretical proximity occurred between Aldo Barreto and his students Maria N. González de Gomez, Regina M. Marteleto and Carlos H. M. Almeida. We observed a steady influence by Pierre Bourdieu and Michel Foucault in the academic genealogy network. We concluded that the Bibliographic Coupling Method contributed to the analysis of the transmission strength of scientific identity in the genealogical lineage of the group of studied researchers.
Indicadores de Acoplamento Bibliográfico para a avaliação da proximidade teórico-metodológica em redes de genealogia acadêmica um estudo aplicado aos descendentes bolsistas PQ de Aldo Barreto
Keywords: Aldo Barreto; Bibliographic coupling; Citation analysis; Information Science; Research grants